Regulation and Anaerobic Function of the Clostridioides difficile β-Lactamase - Sandhu, Brindar K. (Antimicrob Agents Chemother, 2019)
Clostridioides difficile causes severe antibiotic-associated diarrhea and colitis. C. difficile is an anaerobic, Gram-positive sporeformer that is highly resistant to β-lactams, the most commonly prescribed antibiotics. The resistance of C. difficile to β-lactam antibiotics allows the pathogen to replicate and cause disease in antibiotic-treated patients. However, the mechanisms of β-lactam resistance in C. difficile are not fully understood. Our data reinforce prior evidence that C. difficile produces a β-lactamase, which is a common β-lactam resistance mechanism found in other bacterial species. Here, we characterize the C. difficile bla operon that encodes a lipoprotein of unknown function and a β-lactamase that was greatly induced in response to several classes of β-lactam antibiotics. An in-frame deletion of the operon abolished β-lactamase activity in C. difficile strain 630Δerm and resulted in decreased resistance to the β-lactam ampicillin. We found that the activity of this β-lactamase, BlaCDD, is dependent upon the redox state of the enzyme. In addition, we observed that transport of BlaCDD out of the cytosol and to the cell surface is facilitated by an N-terminal signal sequence. Our data demonstrate that a cotranscribed lipoprotein, BlaX, aids in BlaCDD activity. Further, we identified a conserved BlaRI regulatory system and demonstrated via insertional disruption that BlaRI controls transcription of the blaXCDD genes in response to β-lactams. These results provide support for the function of a β-lactamase in C. difficile antibiotic resistance and reveal the unique roles of a coregulated lipoprotein and reducing environment in C. difficile β-lactamase activity.